Mechanical properties of mortar beams reinforced by gyroid 3D printed plastic spatial elements. (November 2022) - Skoratko, Aneta; Szatkiewicz, Tomasz; Katzer, Jacek; Jagoda, Marcin
Abstract: After four decades of technological development, 3-D printing (and other additive manufacturing technologies) is slowly entering research efforts associated with construction and civil engineering. A significant majority of this research effort has focused on 3-D printing of a fresh concrete mix. The authors propose a very different approach for the utilization of 3-D printing in civil engineering based on plastic spatial reinforcing elements for concrete. The mechanical properties of 3-D printed plastics are significantly lower than those of traditional steel re-bars; however, the unconventional and spatial geometric shapes of plastic reinforcement can minimize some of these differences. In the conducted research program, gyroids were harnessed as spatial reinforcing elements that are unachievable using traditional reinforcing techniques. The properties of the tested plastic-mortar elements were highly quasi-plastic and similar to those of good-quality steel fiber-reinforced concrete. The flexural characteristics of plastic-mortar elements enable the testing of possible substitutes for steel reinforcements. Areas of future research and current applications of plastic-mortar elements are discussed.